Growth of cowpea plants inoculated with Rhizobium in a saline-sodic soil after application of gypsum - Angela Jessyka Pereira Brito Fontenele (Revista Ciência Agronômica, 2014)
Two experiments were carried out with the aim of evaluating the growth of cowpea cultivated in saline-sodic soils corrected with gypsum: one experiment in the laboratory, to identify the best level of gypsum for the correction of the saline-sodic soils of the state of Pernambuco, Brazil; and the other in a greenhouse, after correction of the soils. As the test plant, the cowpea cultivar pele de moça , inoculated with Rhizobium strain BR3267 was used. The experiments were arranged in a randomised block design in a 2 x 5 factorial arrangement, two soils and five levels of the gypsum requirement (GR), equivalent to 50, 100, 150, 200 and 250% of the GR of the soil, as determined by the Schoonover M-1 method, with five replications. The following were evaluated: electrical conductivity of the soil saturation extract (EC), soil exchangeable sodium and percentage of soil exchangeable sodium (ESP), number of nodules (NN), nodule dry weight (NDW), shoot dry weight (SDW), shoot height (PH) and nitrogen concentration (N) in the shoots. Application of 100% of the GR, followed by the enough water for leaching, was effective for the correction of soil sodicity. The application of increasing levels of soil GR resulted in an increase in the number of nodules, dry weight of the nodules and shoots, and the height and levels of N absorbed by the plants in soil S2. In soil S1, the use of levels of 200 and 250% of soil the GR caused a decrease in all the variables under study.